2016
DOI: 10.1371/journal.pone.0167277
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Signaling by Singing Humpback Whales (Megaptera novaeangliae): What Role Does Reverberation Play?

Abstract: When humpback whales (Megaptera novaeangliae) sing in coastal waters, the units they produce can generate reverberation. Traditionally, such reverberant acoustic energy has been viewed as an incidental side-effect of high-amplitude, long-distance, sound transmission in the ocean. An alternative possibility, however, is that reverberation actually contributes to the structure and function of songs. In the current study, this possibility was assessed by analyzing reverberation generated by humpback whale song un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Animals that live in highly reverberant, low visibility environments and that often coordinate their movements (e.g., whales and dolphins) would be the most likely to benefit from the use of such cues. Consistent with this possibility, recent analyses of songs produced by humpback whales revealed that individual sounds within their songs also generate reverberant tails that overlap with subsequent sounds, and that ratios of frequencies across consecutive sounds are similar to those found in chickadee songs (Mercado, 2016). Closer examination of correlations between the spectra of sequential sounds produced by other species that acoustically communicate over long distances may further clarify the extent to which such auditory distance cues enable organisms to better coordinate their actions when visual inputs are degraded.…”
Section: Limitations and Future Directionsmentioning
confidence: 73%
“…Animals that live in highly reverberant, low visibility environments and that often coordinate their movements (e.g., whales and dolphins) would be the most likely to benefit from the use of such cues. Consistent with this possibility, recent analyses of songs produced by humpback whales revealed that individual sounds within their songs also generate reverberant tails that overlap with subsequent sounds, and that ratios of frequencies across consecutive sounds are similar to those found in chickadee songs (Mercado, 2016). Closer examination of correlations between the spectra of sequential sounds produced by other species that acoustically communicate over long distances may further clarify the extent to which such auditory distance cues enable organisms to better coordinate their actions when visual inputs are degraded.…”
Section: Limitations and Future Directionsmentioning
confidence: 73%
“…Bats and dolphins make use of a fixed set of sonar signals with specific acoustic properties that have been highly refined through evolutionary processes to yield predictable echoic features ( Simmons and Stein, 1980 ). Singing humpback whales, in contrast, seem to use a more varied repertoire of units, which they produce in an exceptionally wide range of soundscapes; the acoustic properties of units within a song can vary from highly stable to highly dynamic ( Mercado et al, 2010 ; Mercado, 2016 ). Use of ultrasound by bats and dolphins enables them to rapidly extract fine-resolution spatial details from echoes.…”
Section: Song As Sonarmentioning
confidence: 99%
“…Singing humpback whales produce large numbers of units with CF or quasi-CF (minimally FM) components ( Ou et al, 2013 ). In at least some environments, these units can generate spectrally narrow, reverberant bands (overlapping environmental echoes) that persist 10 s or more, such that acoustic energy within the band lasts for as long as the singer repeats a phrase ( Mercado, 2016 ). Units immediately following CF units often contain acoustic energy focused at frequencies just above or just below the CF band ( Figure 5 ).…”
Section: New Evidence Supporting the Sonar Model And Weakening Sexualmentioning
confidence: 99%
See 2 more Smart Citations